Assessment of Spinal Muscular Atrophy Carrier Status by Determining SMN1 Copy Number Using Dried Blood Spots - Yogik Onky Silvana Wijaya; Jamiyan Purevsuren; Nur Imma Fatimah Harahap; Emma Tabe Eko Niba; Yoshihiro Bouike; Dian Kesumapramudya Nurputra; Mawaddah Ar Rochmah; Cempaka Thursina; Sunartini Hapsara; Seiji Yamaguchi; Hisahide Nishio; Masakazu Shinohara (MDPI AG, 2020)
Spinal muscular atrophy (SMA) is a common neuromuscular disease with autosomal recessive inheritance. The disease gene, SMN1, is homozygously deleted in 95% of SMA patients. Although SMA has been an incurable disease, treatment in infancy with newly developed drugs has dramatically improved the disease severity. Thus, there is a strong rationale for newborn and carrier screening for SMA, although implementing SMA carrier screening in the general population is controversial. We previously developed a simple, accurate newborn SMA screening system to detect homozygous SMN1 deletions using dried blood spots (DBS) on filter paper. Here, we modified our previous system to detect the heterozygous deletions of SMN1, which indicates SMA carrier status. The system involves a calibrator-normalized relative quantification method using quantitative nested PCR technology. Our system clearly separated the DBS samples with one SMN1 copy (carrier status with a heterozygous deletion of SMN1) from the DBS samples with two SMN1 copies (non-carrier status with no deletion of SMN1). We also analyzed DBS samples from SMA families, confirmed SMA in the affected children, and determined the carrier status of their parents based on the SMN1 copy number. In conclusion, our system will provide essential information for risk assessment and genetic counseling, at least for SMA families.